Evaluation of the effects of seawater ingress into 316L lined pipes on corrosion performance - Machuca, Laura; Murray, L.; Gubner, Rolf; Bailey, Stuart (Wiley - VCH Verlag GmbH & Co. KGaA, 2014)
The potential effects of seawater ingress into 316L lined pipes during subsea tie-in operations on corrosion performance were investigated. Immersion and accelerated corrosion tests were conducted on 316L in different mixtures of treated seawater. In particular, we examined the effect of oxygen and microorganisms in seawater on the performance of the alloy at the different mixtures of treated seawater to assess the risk of localized corrosion in the event of seawater ingress into pipelines. Results showed that oxygen has a negative impact on the biocidal and oxygen scavenging efficiency of the chemical treatments and a detrimental effect on pitting corrosion.